2012
DOI: 10.5539/ijps.v4n1p158
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Decision Processes in Complex, Ambiguous, Information-rich Environments

Abstract: In order to understand analytic processes in organisations, better tools are required to trace decision processes. An impediment to progress in this area has been the tendency to over-simplify inherently complex information environments or the data that they produce. We address this issue by providing worked examples from the Analysis Simulation Project (ASP). ASP methodology consists of a computer-administered information grid of 64 cells of 50-130 words each. The information accessing activity of participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In line with these recommendations, we developed an experimental methodology known as the Analysis Simulation Project (ASP), which addresses these three recommendations. ASP is a computer administered simulation of complex, dynamic, ambiguous, and uncertain information environments (Wastell, Weeks, & Duncan, ; Weeks, Wastell, Taylor, Wearing, & Duncan, ). These information environments are encountered by many professionals including police officers, security personnel, medical practitioners, and financial advisers.…”
Section: Hypothesis Confirmation As a Positive Test Strategymentioning
confidence: 99%
“…In line with these recommendations, we developed an experimental methodology known as the Analysis Simulation Project (ASP), which addresses these three recommendations. ASP is a computer administered simulation of complex, dynamic, ambiguous, and uncertain information environments (Wastell, Weeks, & Duncan, ; Weeks, Wastell, Taylor, Wearing, & Duncan, ). These information environments are encountered by many professionals including police officers, security personnel, medical practitioners, and financial advisers.…”
Section: Hypothesis Confirmation As a Positive Test Strategymentioning
confidence: 99%
“…Mock investigation studies have provided evidence supporting the idea that individuals develop causal hypotheses in response to complex evidence; particularly once commitment to a choice has occurred, this influences not only search for information but also the processing and evaluation of information that is received (O'Brien, 2009;Simon et al, 2004;Weeks, Wastell, Taylor, Wearing, & Duncan, 2012). Furthermore, interrogator expectations have been shown to influence perceptions of guilt (Kassin, Goldstein, & Savistky, 2009).…”
Section: Choice and Background Knowledgementioning
confidence: 99%
“…Ethics approval for both experiments was obtained from the Macquarie University Human Research Ethics Committee. Materials for this study were presented to participants online, through the survey software Qualtrics and Analysis Simulation Project (ASP; adapted from Weeks et al, 2012). ASP recorded the information accessing activity of participants, including guilt ratings and time spent viewing each piece of evidence.…”
Section: Materials and Apparatusmentioning
confidence: 99%
“…In order to gain a more fine grained understanding of the potential impact of each of the NFC components we have conducted an analogue study of an intelligence analysis type task to explore the role of each NFC dimension on an estimate of threat. The study reported in this paper utilizes the newly developed computer simulation of complex information environments designated ASP-SINTELLA 4 [20] that allows researchers to explore the influence of cognitive variables on analytic tasks while tracking the information processing behaviour used. A fuller description of ASP-SINTELLA is provided in the Appendix.…”
Section: Closed-mindedness and The Yom Kippur War Of 1973mentioning
confidence: 99%